Cry1Ac toxicity enhancement towards lepidopteran pest Ephestia kuehniella through its protection against excessive proteolysis. (15th September 2016) - Elleuch, Jihen; Jaoua, Samir; Tounsi, Slim; Zghal, Raida Z.
Abstract: Bacillus thuringiensis has been extensively used in agroecosystems for four decades due to its high specific toxicity. Strategies based on B. thuringiensis proteins combinations for the improvement of its activity present an important focus for biopesticides development. However, the widespread use of B. thuringiensis δ-endotoxins has often been challenged by a lack of understanding of the target insect physiology as well as its midgut biochemistry. In the present investigation, we have evidenced and explained the toxicity improvement of Cry1Ac δ-endotoxins against Ephestia kuehniella larvae through in vivo combination with P20 helper protein. Tracking the fate of Cry1Ac in tested midgut larvae showed considerable differences between δ-endotoxins produced in the presence of P20 and those produced in its absence which could explain the obtained larvicidal activity enhancement. The P20 presence slightly increased Cry1Ac inclusions solubility in E. kuehniella midgut conditions. However, a protection against excessive degradation of protoxin and toxin forms of Cry1Ac was strongly decreased in the case of δ-endotoxins produced in the presence of P20 as compared to those from P20 lacking control. Thus, the P20 protective effect on Cry1Ac after larvae ingestion has been proven. This finding could be helpful to further understand the roles of P20 helper protein in toxicity enhancement of B. thuringiensis toxins. Graphical abstract: Highlights: Toxicity improvements of Cry1Ac δ-endotoxins through in vivo combination with P20 against Ephestia kuehniella. P20 does not affect Cry1Ac inclusions solubility in E. kuehniella midgut conditions. P20 would protect Cry1Ac protoxins and toxins from proteolytic degradation after larvae ingestion, in the larval midgut.